PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR BEI TAHUN 2018-2020 - Dwi Rantika; Mursidah Mursidah; Yunina Yunina; Zulkifli Zulkifli (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2022)
This study aims to determine the effect of firm size, sales growth, and liquidity on profitability in consumer goods industrial sector companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses secondary data in the form of annual financial statements of consumer goods industry companies listed on the Indonesia Stock Exchange in 2018-2020. This study used purposive sampling in sampling and obtained 32 samples with a total of 96 observations. This research method used a quantitative approach using panel data regression analysis techniques. The results of the study partially have an effect on company size and are not significant on profitability, sales growth has a positive and significant effect on profitability, while liquidity has no and no significant effect on profitability. Simultaneously, company size, sales growth, and liquidity have a significant and significant effect on the profitability of consumer goods industrial sector companies listed on the IDX in 2018-2020.